LATAR BELAKANG FILOSOFIS INTEGRASI AGAMA DAN SAINS DALAM PENGEMBANGAN ILMU PENGETAHUAN MODERN - Hodijah , Siti; Amelia, Putri; M, Amril; Novita, Liana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The relationship between religion and science has long been an important topic in discussions on the development of modern knowledge. While scientific advancement has significantly contributed to human civilization, it has also raised various ethical and moral concerns. One of the contributing factors is the tendency to separate religious values from scientific activities within the modern scientific tradition. This study aims to examine the philosophical background of the integration of religion and science and its relevance to the development of modern knowledge. The research employs a library research approach by reviewing and analyzing various sources related to philosophy of science, Islamic epistemology, and the concept of religion-science integration. The data were analyzed descriptively and critically to explore the intellectual foundations of the integration paradigm. The findings indicate that the integration of religion and science is rooted in the belief that all truth ultimately comes from the same source, namely God. Therefore, revelation and reason should not be viewed as contradictory, but rather as complementary means of acquiring knowledge. The integration of religion and science also promotes a more comprehensive scientific approach by accommodating empirical, rational, ethical, and spiritual dimensions. Consequently, this integration can serve as an important foundation for developing knowledge that is not only academically advanced but also beneficial to humanity as a whole.